Effectiveness Of Pillow Hitting Technique In Controlling Anger In Patients At Risk Of Violent Behavior With Schizophrenia - Tiara ningrum, Putri azizah; Suhanda , Suhanda; Gunawan, Asep (Yayasan Inspirasi El Burhani, 2025)
Introduction: Schizophrenia is a serious mental disorder that can cause disturbances in thinking, emotions, and behavior, including the emergence of violent behavior due to an individual's inability to manage emotions, especially anger. One non-pharmacological approach that can be used to help control anger is pillow-hitting therapy. Objective: This study aims to determine the effectiveness of pillow hitting therapy in controlling anger in schizophrenia patients at risk of violent behavior. Method: The research method used a quasi-experimental design with a pretest-posttest approach and a control group. The study sample consisted of schizophrenia patients at risk for violent behavior, divided into two groups: an intervention group given pillow-hitting therapy, and a control group not given the intervention. Result: The results of the study showed a significant decrease in anger levels in the intervention group after being given therapy. Conclusion: The conclusion of this study is that pillow hitting therapy is effective in helping to control anger in schizophrenia patients at risk of violent behavior, so it can be recommended as a nursing intervention strategy in mental health services.